EXTRACTING DIBS IN THE SPECTRUM OF DOUBLE-LINED SPECTROSCOPIC BINARY STAR HD209481 - Kezia Haans, Gabriela
One of the biggest challenges in the study of ISM is identifying the chemical origins of hundreds of unknown absorption lines, known as the diffuse interstellar bands (DIBs). Single stars have been used vastly as the sample for the study of DIBs. However, as for binary stars, the secondary component is frequently neglected due to blending between star lines and DIBs. Therefore, we present a method of extracting DIBs for the double-lined spectroscopy stars and use HD209481 as our study object. DIBs extraction was performed by reconstructing the spectrum of primary and secondary components using fdbinary/fd3 code, and fitting their synthetic spectra using POLLUX library. As a result, we categorize these DIBs into three groups: (1) Broad and blended DIBs that give a more robust result: DIB ???? 4430, DIB ???? 5494; (2) Unblended DIBs which appear more distinct in the reconstructed spectrum of primary component and the extraction can be performed directly (without reconstructing the spectrum): DIB ???? 4502, DIB ???? 5364, DIB ???? 5487, DIB ???? 5508, DIB ???? 5535, DIB ???? 5545; and (3) DIBs that need to be redefined by redetermining the initial range of ???? in the reconstructing process: DIB ???? 4727, DIB ???? 4762. Additionally, we derive the atmospheric parameters for HD209481: T eff,1 = 31721 K, T eff,2 = 30764 K, [Fe/H] 1 = [Fe/H] 2 = 0.0, log g 1 = 3,55, log g 2 = 3,23, ? 1 = ? 2 = 10 km/s, v rot,1 = 150 km/s, and v rot,2 = 200 km/s.